2019
DOI: 10.1017/s1352465819000377
|View full text |Cite
|
Sign up to set email alerts
|

The influences of virtual social feedback on social anxiety disorders

Abstract: Background:Social feedback in the virtual environment is a critical part of successful virtual reality exposure therapy (VRET), and identifying the influences of virtual social feedback on social anxiety patients is necessary.Aims:The present study aimed to explore the influences of ambiguous and negative virtual social feedback on social anxiety patients and a health control group (HCG).Method:Twenty-six social anxiety patients and 26 healthy participants were recruited. All participants were exposed to a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…In our case, because public speaking is first and foremost a social interaction, the presence sub-concept of social presence is arguably the most important to consider. We can link this to results obtained by Kishimoto and Ding [7], who studied the influences of ambiguous and negative virtual social feedback on anxiety and presence. If no significant differences where found on feels of presence, participants with social anxiety disorders presented higher level of anxiety during public speaking in front of an audience displaying ambiguous feedback compared to an audience with negative feedback.…”
Section: Public Speaking In Virtual Realitysupporting
confidence: 56%
“…In our case, because public speaking is first and foremost a social interaction, the presence sub-concept of social presence is arguably the most important to consider. We can link this to results obtained by Kishimoto and Ding [7], who studied the influences of ambiguous and negative virtual social feedback on anxiety and presence. If no significant differences where found on feels of presence, participants with social anxiety disorders presented higher level of anxiety during public speaking in front of an audience displaying ambiguous feedback compared to an audience with negative feedback.…”
Section: Public Speaking In Virtual Realitysupporting
confidence: 56%
“…When access to information indicative of one's social performance is diminished, discomfort may arise. Research indicates that individuals with SA are particularly susceptible to discomfort elicited by ambiguity (Kishimoto & Ding, 2019;Moscovitch & Hofmann, 2007), and that they are likely to interpret ambiguous cues in negative ways (for a review, see Chen et al, 2020). These negative interpretation biases activated by ambiguous social feedback may be further reinforced by post-event rumination in which individuals with SA selectively focus on negative moments and interpretations from recent social encounters (Gavric et al, 2017;Zou & Abbott, 2012), or remember positive or ambiguous moments in more negative ways (Glazier & Alden, 2019;Romano et al, 2020).…”
Section: Masks As a Barrier To The Interpretation Of Social And Emotional Feedbackmentioning
confidence: 99%
“…Results revealed that positive dialog feedback was associated with significantly less self-reported anxiety, lower heart rate, and longer answers than negative dialog feedback. Similarly, Kishimoto et al [11] instructed 26 individuals with SAD and 26 healthy controls to give two 3-min speeches and examined the impact of ambiguous and negative virtual social feedback. Compared with healthy controls, individuals with SAD reported higher levels of subjective anxiety and the difference was larger in the ambiguous condition than in the negative condition.…”
Section: Virtual Social Worldsmentioning
confidence: 99%